2006
DOI: 10.1016/j.febslet.2005.12.093
|View full text |Cite
|
Sign up to set email alerts
|

Interferon regulatory factor‐1 is prerequisite to the constitutive expression and IFN‐γ‐induced upregulation of B7‐H1 (CD274)

Abstract: Majority of cancer cells upregulate co-inhibitory molecule B7-H1 which confers resistance to anti-tumor immunity, allowing cancers to escape from host immune surveillance. We addressed the molecular mechanism underlying the regulation of cancer-associated B7-H1 expression in response to interferon-c (IFN-c). Using promoter constructs in luciferase assay, the region between 202 and 320 bp from the translational start site is responsible for B7-H1 expression. Electrophoretic mobility shift assay, site-directed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
350
2
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 410 publications
(387 citation statements)
references
References 26 publications
21
350
2
4
Order By: Relevance
“…The observation that INF␥ and Toll-like receptors enhance persistent expression of CD274 in malignant plasma cells by acting via the MyD88, TRAF6, and MAPK signaling pathways (31) supports this conclusion. Finally, the IRS-1 transcription factor has been found to activate the CD274 gene in the lung carcinoma cell line (30). Whether IRS-1 and STAT3 act independently or can cooperate in inducing CD274 expression in at least some types of normal and malignant cells remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that INF␥ and Toll-like receptors enhance persistent expression of CD274 in malignant plasma cells by acting via the MyD88, TRAF6, and MAPK signaling pathways (31) supports this conclusion. Finally, the IRS-1 transcription factor has been found to activate the CD274 gene in the lung carcinoma cell line (30). Whether IRS-1 and STAT3 act independently or can cooperate in inducing CD274 expression in at least some types of normal and malignant cells remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of B7-H1 molecule in the current primary cell lines is not dependent on inflammatory cytokines (g-IFN and TNF-a) known to induce B7-H1. [37][38][39] The similarity in the expression of B7-H1 in fibroblasts and epithelial cell cultures, obtained form either normal or tumor tissues, suggests that B7-H1 is directly related to proliferation and not tumorgenesis (cell transformation). Similarly, Parsa et al have recently found that expression of B7-H1 in human astrocytes was dependent on Akt activation but not on cellular immortalization or transformation.…”
Section: Discussionmentioning
confidence: 99%
“…To further explore the possible mechanism of IL-12 exerts function in regulating B7-H1 expression; we investigated the expression of IFN-γ firstly, because IFN-γ has been well known to induce the expression of B7-H1 (Lee et al, 2005;Lee et al, 2006;Kondo et al, 2010). It was found that rIL-12 and Ad-IL-12-GFP treated groups produced a higher level of IFN-γ in the supernatants of monocyte-derived macrophages cocultured with SKOV3 system.…”
Section: Il-12 Increased the Level Of Ifn-γ And Decreased The Level Omentioning
confidence: 99%